A semantic-based model for the management of people with reduced mobility in airport facilities - Juan José Herrera-Martín; Gonçal Costa; Iván Castilla-Rodríguez; Evelio José González (Egyptian Informatics Journal)
The growing need for inclusive transportation systems has emphasized the importance of addressing the challenges faced by people with reduced mobility (PRM) in airport environments. Nonetheless, its correct performance is subject to different threats and uncontrollable aspects: flight delays, no-show passengers, gate changes, or a high volume of non-registered last-minute PRM passengers, among others. Increasingly, PRM service providers try to deal with such problems by relying on software tools connected to airport information systems to obtain up-to-date data (e.g., flight status, estimated time of arrival or departure of flights, etc.). However, there is no standard representation of the data within this domain that may support the development of aiding tools and enhance their features. To respond to this need, in this article we present an ontology to represent the data domain of PRM services management in airport facilities. The aim is to facilitate the access and combination of the data from different sources under a standardized approach and common understanding of the terminology. The article describes the steps that have been followed to develop the ontology, as well as some usage examples.